Effects of fatty acids on exercise plus insulin-induced glucose utilization in trained and sedentary subjects - Matzinger, O.; Schneiter, P.; Tappy, L. (American Journal of Physiology, Endocrinology and Metabolism, 2002)
Fatty acids are known to decrease insulin-mediated glucose utilization in humans, both at rest and during exercise. To evaluate the effect of endurance training in this process, we infused lipids or saline in groups of sedentary and highly trained subjects. Whole body glucose utilization and substrate oxidation were monitored during a 2.5-h hyperinsulinemic clamp. During the last 30 min, a cycling exercise was superimposed. During hyperinsulinemia at rest, whole body glucose utilization and glucose oxidation were higher in trained subjects than in sedentary subjects. Compared with the control experiments with the antilipolytic agent acipimox, lipid infusion stimulated lipid oxidation to the same extent in trained as in sedentary subjects. It reduced whole body glucose utilization by 37% in trained and by 41% in sedentary subjects. During exercise, lipid infusion increased more lipid oxidation in trained than in sedentary subjects and reduced whole body glucose utilization by 43 +/- 4% in trained and by 22 +/- 4% in sedentary subjects (P < 0.01). The present data indicate that lipid infusion has similar effects on lipid oxidation and whole body glucose utilization during hyperinsulinemia at rest in trained and sedentary subjects. During exercise, however, it increases more lipid oxidation and produces a more important reduction in glucose utilization in trained than in sedentary subjects. These results suggest that endurance training enhances the inhibitory effect of lipids on whole body glucose metabolism during exercise.